Growth, chlorophyll fluorescence, leaf gas Exchange and phytochemicals of Centella asiatica exposed to salinity stress - Ibrahim, Mohd Hafiz; Shibli, Nurul Izzati; Izad, Ayu Azera; Mohd Zain, Nurul Amalina (Sciencedomain International, 2018)
Aims: This study was conducted to investigate the effect of salinity by using a different concentration of sodium chloride (NaCl), on growth, chlorophyll fluorescence and secondary metabolites production of Centella asiatica. Study Design: Centella asiatica plants were exposed to four different concentration of sodium chloride (0, 50, 100 and 150 mM). This research was conducted using a randomized complete block design 4 x 3 with three replications for each treatment and each treatment consists of 12 plants regarding four times harvesting. Place and Duration of Study: Glasshouse of SLAM field, University Agriculture Park, Universiti Putra Malaysia from February to April 2015. Methodology: Salinity stress was induced by irrigating the plants using four salinity levels (0, 50, 100 and 150 mM) of salt concentrations for 12 weeks. The leaves number were counted manually and the total plant biomass was taken by calculating the dry weight of root, stem, and leaf per seedling. The total chlorophyll content in the leaves was measured using a SPAD chlorophyll meter.Chlorophyll fluorescence was measured using Hansatech Pocket PEA, The leaf gas exchange were determined using a LI-6400XT portable photosynthesis system. Total phenolics and flavonoid was determined using Folin-Ciocalteu reagent. Phytochemical screening was conducted to determine the presence of tannin, terpenoids, phenolics, flavonoids, saponin, and alkaloids of plant samples under salinity stress. Results: Increased in salinity levels from 0 > 150 mM, the number of leaves, total biomass and total chlorophyll content were gradually decreased. Centella asiatica exhibit a significant decrease in net photosynthesis (A), transpiration rate (E), maximum efficiency of photosystem II (fv/fm) and Performance index (PI) when the salinity level increased. However, it was noticed that salinity stress significantly enhanced the total phenolic and flavanoid content of C. asiatica. It was also observed,that under salinity there were more presence of phytochemicals (tannin, terpenoids, phenolics,flavonoids, saponin and alkaloids) compared to the control. Conclusion: This study revealed that the increase in salinity level have greatly reduced the growth of C. asiatica but high salinity level also can enhance the production of secondary metabolites (total phenolic and flavonoid content) in C. asiatica.